Biodegradation: A Priority Research Area in Sustainable Development Goals Perspective - Pandey, Anita; Thathola, Pooja (Annals of Arid Zone, 2025)
In the present climate change adaptation scenario, it will be important to prioritize the research areas for present and the times ahead. While prioritizing research areas in developing countries in sustainable development goals perspective, focus should be on the issues like health, food security, clean water, renewable energy, air pollution etc. Further, the emphasis should be on strengthening the local research capacity and the locally relevant research initiatives. It is more pertinent in developing countries where the funds and technologies are limited. In India, one of the major challenges in prioritized research will be the management of waste materials. The preference to the use of plastics has generated serious environmental and human health problems.